Unstable atherosclerotic plaque of the internal carotid artery in the case of a patient with high surgical risk treated endovascularly - Michał Jerzy Terpiłowski; Jędrzej Tkaczyk; Barbara Klatka; Klaudia Brożyna; Magdalena Hołowczuk; Jan Jakub Kęsik; Marek Iłżecki (Kazimierz Wielki University, 2019)
Introduction: Internal carotid artery (ICA) stenosis in a majority is caused by atherosclerotic plaque. Symptoms of ICA stenosis manifest most likely a transient ischemic attack (TIA). The dynamics of ICA stenosis progression is unpredictable, the disease may progress quickly or slowly or remain stable for many years. The method of treatment implemented also depends on it. The task of pharmacological treatment is to reduce the progression of the disease and protect against the onset of stroke. Among the invasive methods of treating ICA stenosis, the standard procedure is endarterectomy of a carotid artery (CEA), i.e. surgical removal of atherosclerotic plaque. Another method of treatment is endovascular carotid artery stenting (CAS). CAS should be considered especially in the case of re-operated patients, also after radiotherapy and tracheostomy. CAS is a less invasive procedure, it avoids complications typical for CEA such as cranial nerve palsy or complications at the site of the wound. On the other hand, the risk of postoperative ischemic stroke is greater in the case of CAS. In recent years, the improved CAS method seems to be the implantation of dual-layered mesh-covered carotid stent systems (DLS). Case report: We present the case of a 69 old man, long-term smoker, with hypertension and coronary heart disease. In 2001 diagnosed with larynx cancer and underwent surgical laryngectomy and radiotherapy. He was admitted in scheduled mode due to symptomatic carotid artery stenosis. In USG examination there was visible stenosis of the right internal carotid artery (80%) caused by an unstable atherosclerotic plaque with irregular structure and thrombotic clots. Due to the obvious difficulties of performing endarterectomy following radiotherapy in the neck area and laryngectomy, the endovascular method has been considered. In spite of the unstable plaque, which is a contraindication to perform the endovascular procedures CAS has been decided to perform. The patient underwent implantation of a dual-layered carotid stent in the combination with proximal balloon occlusion protection with a MoMa device. After procedure arteriography confirmed the optimization of the carotid artery flow and the correct position of the stent. The treatment was carried out without complications. After a few days of hospitalization, the patient was discharged home. Discussion: The method of treatment of internal carotid artery stenosis is selected taking into consideration morphology and localization of atherosclerotic plaque, anatomical conditions and the local condition of the surgical area as well as the general condition of the patient and coexisting diseases. On the one hand, the patient underwent cervical radiotherapy and laryngectomy which are contraindications for CEA. On the other hand, an atherosclerotic plaque was unstable with the features of stratification which is a contraindication to the performance of CAS. In the described case it was decided to make implantation of dual-layered carotid stent system (DLS) connected with proximal balloon occlusion protection with a MoMa device allowed to reduce the risk of embolization.